ChemoProtective effects of new iodine coordinated compound in benzo[a]pyrene- induced lung cancer in BALB/c mice - Abekova Assima; Islamov Rinat (BIO Web of Conferences, 2024)
Iodine preparations are widely used in medicine as antiseptic agents. One of the new directions for the use of iodine is the prevention and therapy of certain tumor diseases, particularly breast cancer. The main mechanism of action is the induction of apoptosis. Iodine also has anti-inflammatory activity and affects the polarization of Th1/Th2 lymphocytes and M1/M2 macrophages. The newly developed iodine complex KC-144 includes both dextrin and polypeptides. In this case, lithium enhances the polarization of triiodide. We studied the acute toxicity and prophylactic activity on a model of benz(a)pyrene-induced (BaP) tumor in BALB/c mice. The average lethal dose (LD50) of KC-144 when administered orally was more than 2500 mg/kg, classifying KC-144 as a low-toxicity substance. Intraperitoneal administration of benz(a)pyrene at a dose of 100 mg/kg for two weeks induces tumor development in mice. Oral administration of KC-144 at doses of 2.5 and 25 mg/kg for one week and throughout the entire treatment period increases the lifespan of BaP-induced mice.